An analysis of the influence and mechanisms of the digital economy on the disparities in urban total factor productivity - Liu, Yang; Zhang, Yabing (Technological and Economic Development of Economy, 2025)
The influence of the digital economy (DE) on the coordination of the urban total factor productivity (TFP) gap and its underlying mechanisms were investigated. The significance of this research mainly originates from its contribution to the theoretical understanding of regional coordination mechanisms, offering new insights into how the digital economy internally regulates disparities in regional TFP. Key findings include: (1) The dynamic analysis reveals that during the early stages of DE, the urban TFP gap expands significantly. However, as the digital economy matures, it contributes to reducing this gap. (2) Quantile regression results indicate that the digital economy substantially narrows the TFP gap primarily in regions with the most pronounced disparities (comprising 20% of the sample), while this effect is not evident in the remaining 80% of regions. (3) Enhancing the level of marketization of factors significantly strengthens the digital economy’s ability to reduce the TFP gap, and improvements in resource allocation also contribute to this effect. First published online 06 June 2025